Bacillus subtilis as a robust host for biochemical production utilizing biomass - Park, Seo A.; Bhatia, Shashi Kant; Park, Hyun A.; Kim, Seo Yeong; Sudheer, Pamidimarri D.V.N.; Yang, Yung Hun; Choi, Kwon Young (Critical Reviews in Biotechnology, 2021)
Bacillus subtilis is regarded as a suitable host for biochemical production owing to its excellent growth and bioresource utilization characteristics. In addition, the distinct endogenous metabolic pathways and the suitability of the heterologous pathways have made B. subtilis a robust and promising host for producing biochemicals, such as: bioalcohols; bioorganic acids (lactic acids, α-ketoglutaric acid, and γ-aminobutyric acid); biopolymers (poly(γ-glutamic acid, polyhydroxyalkanoates (PHA), and polysaccharides and monosaccharides (N-acetylglucosamine, xylooligosaccharides, and hyaluronic acid)); and bioflocculants. Also for producing oligopeptides and functional peptides, owing to its efficient protein secretion system. Several metabolic and genetic engineering techniques, such as target gene overexpression and inactivation of bypass pathways, have led to the improvement in production titers and product selectivity. In this review article, recent progress in the utilization of robust B. subtilis-based host systems for biomass conversion and biochemical production has been highlighted, and the prospects of such host systems are suggested.
Keywords: Engineering techniques; Functional peptides; Gamma-aminobutyric acids; N-Acetylglucosamine; Polyhydroxyalkanoates; Product selectivities; Protein secretion system; Xylooligosaccharides; Bacillus subtilis; Biomass; Genetic Engineering; Metabolic Engineering; Metabolic Networks and Pathways; Peptides; Bacillus subtilis; bioorganic acids; biopolymer; biosugar; functional peptides; surfactant; surfactin